2018
DOI: 10.32734/tm.v1i3.256
|View full text |Cite
|
Sign up to set email alerts
|

Kandungan Total Flavonoid Dari Ekstrak Metanol Akar Imperata cylindrical (L) Beauv. (Alang-alang)

Abstract: Masyarakat di Sulawesi Tenggara telah memanfaatkan akar alang-alang (Imperata cylindrica) sebagai obat hipertensi. Ekstrak methanol akar alang-alang dari Kendari terbukti mempunyai aktivitas antihipertensi. Studi menunjukkan senyawa-senyawa fenolat dapat menurunkan tekanan darah. Aktivitas penurunan tekanan darah dikarenakan senyawa-senyawa fenolat mempunyai aktivitas antioksidan dan kemampuan menghambat angiotensin converting enzyme (ACE). Berdasarkan penelitian yang dilaporkan, tujuan penelitian ini menentuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Dhianawaty measured the total flavonoid content by using aluminum chloride method, and the results showed that the extract contained flavonoids, with a total content of 1.17%. 32 Flavonoids consist of a large group of polyphenolic compounds having a benzo-ɤ-pyrone structure with many biological activities such as antioxidant, antibacterial, anti-inflammatory, antiviral, anticancer and hepatoprotection. 33 Several mechanisms have been proposed for the effect of flavonoids on the initiation and promotion stages of carcinogenesis, including the development and hormonal activities through downregulation of mutant p53 protein, cell cycle arrest, tyrosine kinase inhibition, inhibition of heat shock proteins, estrogen receptor binding capacity, and inhibition of expression of Ras proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Dhianawaty measured the total flavonoid content by using aluminum chloride method, and the results showed that the extract contained flavonoids, with a total content of 1.17%. 32 Flavonoids consist of a large group of polyphenolic compounds having a benzo-ɤ-pyrone structure with many biological activities such as antioxidant, antibacterial, anti-inflammatory, antiviral, anticancer and hepatoprotection. 33 Several mechanisms have been proposed for the effect of flavonoids on the initiation and promotion stages of carcinogenesis, including the development and hormonal activities through downregulation of mutant p53 protein, cell cycle arrest, tyrosine kinase inhibition, inhibition of heat shock proteins, estrogen receptor binding capacity, and inhibition of expression of Ras proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu flavonoid memiliki aktivitas menginhibisi enzim ACE, sehingga menyebabkan terbentuknya kompleks khelat di pusat aktif ACE, dan bergantung pada fitur struktural utama dari senyawa flavonoid. Sehingga kandungan senyawa flavonoid dalam ekstrak serta aktivitasnya sebagai antioksidan membuktikan bahwa senyawa flavanoid tersebut memiliki kemampuan sebagai vasorelaxan [17].…”
Section: Hasil Uji Aktivitas Vasorelaxanunclassified
“…Imperata cylindrica (hereinafter referred to as I. cylindrica) is a weed plant, in Indonesia it grows in over 8.5 million ha areas [1,2]. In traditional medicines it has positive roles for health, such as to treat wound and to prevent hypertension, tonic drink for health, urinary stones, fever, cough, etc [1][2][3].…”
Section: Introductionmentioning
confidence: 99%